Actual nutrition and dietary supplementation in Lithuanian elite athletes - Baranauskas, M.; Jablonskiene, V.; Abaravicius, J. A.; Stukas, R. (Medicina, 2020)
Background and objectives: Health is partly determined by the state of one`s nutrition; it stimulates the body`s functional and metabolic adaptations to physical strain and helps one prevent sports injuries and get in shape in terms of body composition. This study aims to investigate the actual nutrition and dietary supplements taken by elite Lithuanian athletes and to identify the relationship between the dietary intake, dietary supplementation and body composition of elite athletes. Materials and Methods: The research subjects were 76.7% of Lithuanian elite athletes (N = 247). The actual diet was investigated using the 24 h recall dietary survey method. Dietary supplementation was studied applying the questionnaire method. Measurements of body composition were performed using the BIA (bioelectrical impedance analysis) tetra-polar electrodes and measuring resistivity with 8-12 tangent electrodes at different frequencies of signal: 5, 50 and 250 kHz. Results: Results indicate that among the athletes, 62% use too few carbohydrates and 77% use too much fat. Although the 3.5% increase in lean body mass (95% CI: -0.107, 7.070) helps gain an increased protein intake with food (p = 0.057), 38% of athletes consume too little protein with food. The athletes mostly use carbohydrates (86%), vitamins (81%), protein supplements (70%), and multivitamins (62%). We did not determine the impact (p > 0.05) of individual or complex supplement use on the lean body mass (%) or fat mass (%) values of athletes. Conclusions: Athletes consume insufficient carbohydrates, vitamin D, calcium, polyunsaturated fatty acids, omega-3 and omega-6 fatty acids and too much fat, saturated fatty acids, cholesterol, and they use proteins irrationally. Sport nutritionists should also focus on the risk of malnutrition for female athletes. Nutritional supplements partially offset macronutrient and micronutrient deficiency. Nevertheless, the effect of food supplements on the body composition of athletes is too small compared to the normal diet. Athletes ought to prioritize the formation of eating habits and only then use supplements.